If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 = -34 Reorder the terms: 14 + 2x = -34 Solving 14 + 2x = -34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = -34 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = -34 + -14 2x = -34 + -14 Combine like terms: -34 + -14 = -48 2x = -48 Divide each side by '2'. x = -24 Simplifying x = -24
| 4b-17= | | t/3-2=10 | | 0.13/0.2 | | 20x+14=34 | | 6S+S=245 | | -20x+14=34 | | 5x+26=16 | | 15.3+h=1.3-h | | x=1/3x=8 | | 4x+2(3x-5)=5x+14-7x | | X-3=25-10 | | 3xy+x+y=0 | | 441.5+x=22 | | u+4.6=9.17 | | h=x^2-8ln-2 | | tan(2pi+x)= | | h(x)=x^2-8ln-2 | | 8x+19=-28-8x | | -2w+8=-56 | | 5p^2+6p+1=O | | (y+9)2*2-(y+5)2*2=28 | | -7u-46=31 | | h(t)=-16t^2+36t+5 | | Y-8=2/3x | | 6d+57=39 | | 2x+3=2x-(3x+2x)+6 | | -6(-4x+3)-5x=7(x-2)-1 | | -5a+(-18)=22 | | -2(3+x)+3(2+2x)=1+4x | | 10x-3y-5x+13y= | | 10xsquare-3x-1=0 | | 2p-(-86)=52 |